PENGARUH CITRA KEAMANAN DESTINASI TERHADAP KUNJUNGAN WISATAWAN NUSANTARA KE YOGYAKARTA - Reksapati, Abadi (JURNAL NASIONAL PARIWISATA, 2013)
The research aims to: first analyze the perception of travelers towards security image as tourism destination Yogyakarta tourism. Both explained the background to the perception of travelers towards Yogyakarta tourism image, (second, explain the background of the travelersâ perception towards Yogyakarta tourism image) and the third describes the influence of perceived security image Yogyakarta tourism on tourist visitation. (And the third describe the influence of the perception of Yogyakarta tourism security image on tourist visitation) Research carried out by domestic tourists to explore the perceptions of crime and the threat of natural disasters. The research process conducted by distributing questionnaires to 100 tourists in four locations: Malioboro, Parangtritis, Gembira Loka Zoo and Prambanan temple in the period May-June 2011.Â From (based on) the results of the study found that knowledge of the origin of tourists and travelers do not have significant differences in perceived security image in Yogyakarta. This is in contrast to the type of traveler experience find significant differences occurred in perceiving security image Yogyakarta. The study also found that the perception of tourists visiting Yogyakarta during the period by the study is more influenced by the level of crime compared to the natural disaster.Â The conclusions of this research areas a general tourist destination Yogyakarta has had a positive mental map in the eyes of tourists, so the threat of natural disasters and the high level of crime is not easy to change the Yogyakarta positive image in the eyes of tourists easily. Furthermore, this study recommends Yogyakar tatourism stakeholders to improve the system security by maximizing tourist attractions as well as internal security assistance fromthe police. Meanwhile, toimprove thesecurity of travelers associated with natural disasters, crisis management should be designed toprovide a guarante to tourists.Â